The values of wildlife revisited - Gomez, J.; Vliet, N. van; Canales, N. (Resilience Alliance, Inc., 2022)
Wild animals are important worldwide because of the multiple values they represent for human societies. Different frameworks have been proposed to understand the values of wildlife from economic and noneconomic perspectives. Despite efforts from different disciplines to provide a holistic framework for the analysis of wildlife values, the focus is still based on the monetary value derived from market prices. Community-oriented approaches to wildlife conservation have an especially strong economic rationale because they depend on the economic costs and benefits that wildlife represents to local communities. However, purely economic approaches ignore that values are subjective and as such are perceived differently among stakeholders according to their social, economic, cultural, and ecological context. The lack of a holistic framework hinders the possibility to provide a clear and practical tool for the resolution of wildlife conservation conflicts and the identification of management options that maximize values. Based on a wide literature review, we propose a comprehensive wildlife value framework (WVF) incorporating the values of wildlife identified in the academic literature into the total economic value (TEV) framework. Costs associated with human-wildlife conflicts are also incorporated as well as subjective perceptions of values based on multidimensional well-being criteria. This work aims to provide a common structure within which different perspectives related to wildlife can be captured to inform multi-actor, multi-objective decision making related to wildlife management.